Ecosystem Climate and Digital Library Transformation at Indonesian Agency for Agricultural Standardization (IAAS) - Rushendi; Majidah Majidah (Alexandria: Journal of Library and Information Science, 2024)
Libraries as information resource centers certainly have librarians/library managers who can manage and serve the community in a valid and up-to-date manner. Librarians in the era of the digital ecosystem are expected to be able to accelerate themselves to become an integral part of providing optimal service to users. The purpose of the study is to determine the ecosystem climate and digital library transformation at the Indonesian Agency for Agricultural Standardization (IAAS). The study was designed in a qualitative descriptive manner using a survey method of librarians/library managers totaling 39 respondents. Data were collected and analyzed using the standard deviation in Microsoft Office Excel 2010 with the implementation of the July 2022 – June 2023 study. The results of the study found that the characteristics of librarians/library managers were mostly male aged 25-50 years with strata 1 education level. The level of understanding of librarians/managers library towards digital knowledge is high but the level of embedded knowledge is low. The climate for the digital transformation ecosystem is still in processing activities with the development stage on websites, mobile apps, databases and cloud computing. For technological advances, it is hoped that librarians/library managers will be more literate and more innovative in the future development of digital libraries.